Characterization of the Plasmodium falciparum and P. berghei glycerol 3‐phosphate acyltransferase involved in FASII fatty acid utilization in the malaria parasite apicoplast. (1st August 2016) - Shears, Melanie J.; MacRae, James I.; Mollard, Vanessa; Goodman, Christopher D.; Sturm, Angelika; Orchard, Lindsey M.; Llinás, Manuel; McConville, Malcolm J.; Botté, Cyrille Y.; McFadden, Geoffrey I.
Summary: Malaria parasites can synthesize fatty acids via a type II fatty acid synthesis (FASII) pathway located in their apicoplast. The FASII pathway has been pursued as an anti‐malarial drug target, but surprisingly little is known about its role in lipid metabolism. Here we characterize the apicoplast glycerol 3‐phosphate acyltransferase that acts immediately downstream of FASII in human ( Plasmodium falciparum ) and rodent ( Plasmodium berghei ) malaria parasites and investigate how this enzyme contributes to incorporating FASII fatty acids into precursors for membrane lipid synthesis. Apicoplast targeting of the P. falciparum and P. berghei enzymes are confirmed by fusion of the N‐terminal targeting sequence to GFP and 3′ tagging of the full length protein. Activity of the P. falciparum enzyme is demonstrated by complementation in mutant bacteria, and critical residues in the putative active site identified by site‐directed mutagenesis. Genetic disruption of the P. falciparum enzyme demonstrates it is dispensable in blood stage parasites, even in conditions known to induce FASII activity. Disruption of the P. berghei enzyme demonstrates it is dispensable in blood and mosquito stage parasites, and only essential for development in the late liver stage, consistent with the requirement for FASII in rodent malaria models. However, the P. berghei mutant liver stage phenotype is found to only partially phenocopy loss of FASII, suggesting newly made fatty acids can take multiple pathways out of the apicoplast and so giving new insight into the role of FASII and apicoplast glycerol 3‐phosphate acyltransferase in malaria parasites.